Influences of storage conditions on germination of Bittergourd (Mormodicacharantia) seeds - Atputhachandran, P.; Sivachandiran, S. (Jaffna Science Association Annual Session – 2008, 2008)
Bitter gourd is an important vegetable crop for its quality and medicinal value. Poor germination after storage is reported by seed producers as well as farmers as the major hindrance in increasing production. An experiment was carried out at the Faculty of Agriculture, University of Jaffna to evaluate the viability of bitter gourd seeds under different storage conditions with and without hot water treatments. Pods harvested within a week interval from selected farms were used for the study. Seeds were air dried under shade and stored at four different storage conditions, paper bag, cloth bag, polythene bag and refrigeration. Germination test was carried out at two weeks intervals with and without hot water treatment. Results indicated that paper bags are more suited to store bitter gourd seeds for short period. Germination percentage of all seeds decreased after four weeks of storage irrespective of storage condition. However polythene bags will retain the viability and suited to store seeds up to ten weeks under ambient condition. Warm water treatment was effective to enhance germination of bitter gourd seeds. Refrigeration is not much suited to store bitter gourd seeds. If they stored under refrigeration they must be treated with warm water prior to plant them to the field